Rapid determination of diesel/biodiesel blend ratio using refractive index, density, and kinematic viscosity measurements - Siti Norhafiza, Mohd Khazaai; Bhuyar, P.; Mohd Hasbi, Ab. Rahim; Muhammad Hasnol Fazirin, Mohd Alwi; Yiting, Sih; Maniam, Gaanty Pragas (Springer, 2021)
Biodiesel is considered as one of the most sustainable alternative form of bioenergy to overcome and compensate the detrimental effect of fossil fuel. Blending of biodiesel into diesel fuel at specific fractions has been mandated in various countries. In this regard, the present study is intended to observe an appropriate proportion of blending of palm, olive, and soybean-based biodiesel based on respective refractive index, density, and kinematic viscosity analysis. Among the tested parameters for the blend fraction of B7 to B100, refractive index and density exhibited many accurate results with % error < 0.65% for all blends. Good linearity is observed for all three tested parameters with R2 values between 0.892 and 0.985, hence validating them as indicators for the determination with strong relationship within variables. Rapid determination of blend ratio in diesel–biodiesel blends in a shorter possible time benefits the related industries and monetary gain in countering any false claim on the % blend.